IEEE INFOCOM 2008 - The 27th Conference on Computer Communications 2008
DOI: 10.1109/infocom.2008.61
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Down Skype Traffic

Abstract: Abstract-Skype is beyond any doubt the most popular VoIP application in the current Internet application spectrum. Its amazing success drawn the attention of telecom operators and the research community, both interested in knowing Skype's internal mechanisms, characterizing traffic and understanding users' behavior.In this paper, we dissect the following fundamental components: data traffic generated by voice and video communication, and signaling traffic generated by Skype. Our approach is twofold, as we make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 3 publications
1
32
0
Order By: Relevance
“…We use a simple, custom fragmentation/reassembly protocol similar to IP fragmentation to manage fragmented chunks. 2 In the figure we can see that probe packets in (ii) carry a single, fragmented TCP segment, whose chunks are labeled 2a and 2b. If MGRP cannot piggyback an entire rider before the buffer timeout, MGRP simply sends the chunk in its own MGRP packet, shown as (iii) in the figure.…”
Section: Basic Operationmentioning
confidence: 99%
“…We use a simple, custom fragmentation/reassembly protocol similar to IP fragmentation to manage fragmented chunks. 2 In the figure we can see that probe packets in (ii) carry a single, fragmented TCP segment, whose chunks are labeled 2a and 2b. If MGRP cannot piggyback an entire rider before the buffer timeout, MGRP simply sends the chunk in its own MGRP packet, shown as (iii) in the figure.…”
Section: Basic Operationmentioning
confidence: 99%
“…The same authors later proposed OneClick [6], a lightweight framework for measuring network applications' quality of experience from users' perspective, in the hope to verify the passive measurement results by user experiments. Bonfiglio et al [3] analyzed how Skype adapts its traffic to different network conditions. They found that when available bandwidth is decreased, the bit rate and payload size of Skype traffic are also decreased.…”
Section: Related Workmentioning
confidence: 99%
“…How Skype adapts to changing bandwidth has been discussed in [3]. The authors have found that when they reduced the bandwidth, the payload size decreased, which suggests the codec switches to a lower bit rate.…”
Section: A Effect Of Available Bandwidthmentioning
confidence: 99%
See 1 more Smart Citation
“…Broadly speaking, current techniques either passively observe existing traffic, or actively inject probe packets to see how the network responds. Using passive measurement, an application may observe the rate at which its buffers fill or empty [10] and monitor the rates of packet and frame loss [2,3]. Passive observations are particularly useful for signaling that a stream's rate should be reduced, but do little to suggest when its rate can be increased [2,3].…”
Section: Introductionmentioning
confidence: 99%